Gulf remittances & spending behavior of migrant Muslim households in Wandoor block, Malappuram district, Kerala - K.T , Basheer; Rafeeq , Dr. B. Mohamed (International Journal of Accounting and Economics Studies, 2025)
The research intends to expose that the operational financial activities of Gulf households should be studied on the quantitative basis, which has been based on quantitative data from 313 participants. The researcher was able to extract some crucial themes, including households’ balanced spending and saving habits, the impact of remittances on household finances, and the likelihood of socioeconomic characteristics such as education and residence on financial decisions. Even though the relation shows that a strong association exists between remittance and household consumption, a causative relationship needs to be studied further. Regression models show that a significant impact on the level of spending tendency is of the highest value, for the medium and the high value, and for the low value of the variable of remittance amount. However, the models indicate that more elements need to be integrated in order to get a proper understanding. This study lays the foundation for future research using bigger and more varied populations in examining a broader variety of financial parameters and causal relationships. Implications from the study seem to extend far beyond understanding financial practices to aspects of designing targeted interventions and measurements to increase financial security and stability in the Gulf area.